The synthesis and characterization of hydroxylapatite microtubules/polylactic acid GTR membranes and its effect on periodontal bone regeneration - Junyan, Wang (2024)
The general objective of the study is to develop novel hydroxylapatite microtubules/PLA GTR membranes and evaluate them for mechanical and biological properties. HAp microtubules were prepared through hydrothermal synthesis. The composition and morphology of the synthesized materials were examined by a scanning electron microscope (SEM), transmission electron microscopy (TEM), Xray powder diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). Then the novel hydroxylapatite microtubules/PLA GTR membranes were fabricated. The membranes were verified whether they met the clinical mechanical requirements in degradation and stretching properties. In addition, we examined its interaction with human periodontal ligament stem cells (hPDLSCs), harvested from healthy teeth. The osteogenic effect of the membrane on hPDLSCs was examined by evaluating the gene and protein expressions of the RUNX2, OPN, and OCN using Quantitative PCR (qPCR) and Western blotting analysis, respectively. In this study, all data for the mechanical property tests, which include water contact angle tests, tensile tests, swelling analysis and biodegradation analysis were expressed as mean and standard deviation. For cell proliferation and osteogenic differentiation experiments, the data were numerical. The normality of distribution was assessed using Q-Q plot analysis. In some cases, natural log transformation was employed to aid in representing data that exhibited normal distribution. The significance level was set at p = 0.05. The HAp microtubules/PLA membrane had better tensile and breaking strengths and lower fracture productivity than the PLA membrane. The expansion rate reached 34% after 2 h, and the degradation rate exceeded 25% after 40 days. Water contact angle measurement results showed that the bilayer membrane was hydrophilic on one side and hydrophobic on the other side. The results of the cell experiments also showed that the membrane had no cytotoxicity. The number of cells in the HAp microtubule/PLA membrane group was found to be significantly higher than that observed in the group with a PLA membrane (p<0.05). Furthermore, the expression of genes and proteins associated with bone composition was significantly elevated in the HAp microtubule/PLA membrane group compared to the HAp powder/PLA membrane and hPDLSCs group (p<0.05). The HAp microtubule side can promote the expression of genes and proteins related to osteogenesis, while the PLA side can inhibit cell adhesion. The HAp microtubules/PLA membrane has stability and good mechanical properties. The double-layer structure has the function of a biological barrier and promotes bone formation.